Effect of colemanite on properties of traditional mullite zirconia composite. Issue 1 (31st December 2016) - Aydın, H.; Gören, R.
Abstract: In this study, mullite zirconia composites are synthesized via reaction sintering method by using zircon, kaolinite and alumina mixtures including colemanite (Ca2 B6 O11 5H2 O) (7 wt.%). In mullite zirconia composites, the effect of colemanite additive on mineralogical, thermal, microstructure and mechanical properties and also on formation are studied. Mixtures are sintered at 1, 450, 1, 500 and 1, 550°C for 5 h. in air. The resulting sintered materials are characterized in terms of bulk density, DTA, X-ray diffraction (XRD), SEM and mechanical properties such as flexural strength and elastic modulus. Various effects of colemanite addition on the composites are observed with regard to thermal, mineralogical and mechanical properties. Both DTA and XRD analyses show that colemanite addition in mullite zirconia composite reduces the reaction temperature. Zircon alone in the mixture resulted in a 1, 550°C reaction temperature, whereas the compositions including colemanite is attenuated to 1, 450°C. While zircon exists up to 1, 550°C in the mixtures free of colemanite, it decays at 1, 450°C due to 7 wt.% colemanite addition. Composites comprising of 7 wt.% colemanite exhibit a higher density, flexural strength ( σ ) and elastic modulus ( E ). Microstructural characterization of the sintered samples through scanning electron microscope indicate mullite and zirconia are the two main phases. Homogenously distributed round-shaped ZrO2 grains and irregularly shaped mullite grains are observed, which fundemantally constitute the microstructure.